Disadvantaged but different: variation among deprived communities in relation to child and family well-being. - Barnes, J; Belsky, J; Broomfield, K; Dave, S; Frost, M; Melhuish, E (2005)
BACKGROUND: Disadvantaged communities are increasingly the target for interventions. Sure Start was launched in England in 1999 to tackle child poverty and improve child and family services, with Sure Start Local Programmes (SSLPs) targeted at relatively small areas of marked deprivation. However, they are located in a range of different types of communities where they may provide services to very different resident populations. They are all disadvantaged but underlying that label there are specific patterns of variability, relevant for service provision. To evaluate the implementation, impact, and cost-effectiveness of SSLPs, or other area-based initiatives, it is important to consider ways in which they can be grouped meaningfully according to these patterns. METHOD: Data were collected from administrative databases to describe SSLPs in terms of demography, deprivation, and aspects of child and family functioning and grouped using cluster analysis. RESULTS: Five different 'types' of SSLP community were identified, based on their socio-demographic and economic characteristics; typified by more, less or average deprivation in relation to all SSLPs, and in terms of the proportion of ethnic minority families resident in the areas. The groups differ in terms of community measures of child health, educational attainment, school disorder and child welfare and their prediction from demographic community characteristics. CONCLUSIONS: The groupings have implications for service delivery and the evaluation of area-based initiatives.